The Influence of Emotional Intelligence and Perceived Organizational Support on Employee Performance Through Job Satisfaction - Fadlilah, Mazidatul; Wardoyo, Dewie Tri Wijayati; Surjanti, Jun (Transpublika Publisher, 2025)
The primary objective of this research is to examine how emotional intelligence, perceived support from the organisation, and satisfaction with one's job can impact the performance of employees, with a particular focus on the role of job satisfaction as a mediator in this process. In total, 227 participants from the workforce of a specific company were involved in the study. Responses were gathered through a survey with closed-ended questions rated on a 1-to-5 Likert scale, indicating differing levels of agreement. Analysis of the data was carried out using Structural Equation Modelling (SEM) with the use of AMOS software version 22. The findings of the research suggest that: (1) Employee performance is deeply impacted by emotional intelligence; (2) Emotional intelligence plays a role in determining job satisfaction; (3) The perception of organisational support has an impact on performance; (4) The perception of organisational support also influences job satisfaction; (5) Employee performance can be affected by job satisfaction; (6) Job satisfaction acts as a mediator between emotional intelligence and performance; and (7) Job satisfaction also acts as a mediator between perceived organisational support and performance. These findings highlight the importance of establishing a supportive work environment that fosters emotional and organisational well-being to enhance employee performance. The practical implications of this study for human resource management involve developing strategies to boost employee performance by enhancing emotional intelligence and strengthening perceptions of organisational support.